Cellular site of gastric acid secretion. - DiBona, D R (1979)
Isolated gastric glands of the rabbit were examined both with differential interference-contrast microscopy and with electron microscopy to describe the morphologic correlates of acid secretion. Stimulation of the glands with histamine resulted in the development of intracellular spaces within the parietal cells. A similar transformation was produced by addition of 1 mM aminopyrine, whether the weak base was added in the presence of normal-K+ (5.4 mM) or high-K+ (108 mM) solutions. The intracellular space was compatible with the expanded canaliculus described in stimulated parietal cells. Confirmation that the space produced by histamine is the site of acid secretion was gained by combining fluorescence and interference-contrast methods in the presence of the dye acridine orange, which displays a pH-dependent metachromasia in its emission spectrum. Human gastrin I resulted in an observable discharge of peptic granules.